Ferroptosis‐associated cholesterol metabolism regulated by p85α in human bronchial epithelial cells with smoking. Issue 1 (20th February 2022) - Li, Liyang; Wang, Xiangdong
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterized by inflammation, airflow obstruction, and lung damage resulting from multiple causes, in particular the exposure to cigarette smoke. Growing evidence supports an important role for lipid metabolism in the development of COPD, where ferroptosis plays a critical role in lipid metabolism and cholesterol homeostasis. The aim of the present study was to investigate the role of cigarette smoke extract (CSE) in the induction and formation of ferroptosis and its potential relation with intracellular cholesterol accumulation. Methods: Filipin III staining and cholesterol content assay kit were used to detect intracellular cholesterol level. BODIPY C11 581/591 and malondialdehyde (MDA) assay kit were used to detect lipid perioxidation. Quantitative RT‐PCR was used to detect the mRNA level of ferroptosis‐related and cholesterol‐related genes. The protein expression of phosphatidylinositol 3‐kinase (PI3K) signaling pathway and related proteins were analyzed by Western blot. Results: We found that CSE and exogenous cholesterol induced ferroptosis, while the ferroptosis agonist increased intracellular cholesterol levels. The inhibition of ferroptosis activated the cholesterol efflux and synthesis. We also found regulatory roles of PI3K/AKT pathway, especially the role of p85α, in the development of ferroptosis. Conclusions: CSE‐induced ferroptosis in human bronchial epithelia changed intracellular cholesterol homeostasis. The interaction between cholesterol metabolism and ferroptosis may play an important role in the development of COPD. Abstract : 1. Cigarette smoke extract (CSE) stimulated the occurrence of ferroptosis in human bronchial epithelia (HBEs), associated with the interactions with intracellular cholesterol accumulation. 2. p85α and the phosphatidylinositol 3‐kinase (PI3K)/AKT pathway participated in the regulation of the CSE‐induced ferroptosis in HBEs.